Pattern and scale of geographic variation in environmental sex determination in the Atlantic silverside, Menidia menidia. (1st August 2015) - Duffy, Tara A.; Hice, Lyndie A.; Conover, David O.
Abstract: The Atlantic silverside, Menidia menidia (Pisces: Atherinidae), exhibits an exceptionally high level of clinal variation in sex determination across its geographic range. Previous work suggested linear changes in the level of temperature‐dependent sex determination (TSD) with increasing latitude. Based on comparisons at 31 sites encompassing the entire species' range, we find that the change in level of TSD with latitude is instead highly nonlinear. The level of TSD is uniformly high in the south (Florida to New Jersey), then declines rapidly into the northern Gulf of Maine where genotypic sex determination (GSD) predominates and then rebounds to moderate levels of TSD in the northern‐most populations of the Gulf of St. Lawrence. Major latitudinal breakpoints occur in central New Jersey (40 o N) and the northern Gulf of Maine (44 o N). No populations display pure TSD or GSD. Length of the growing season is the likely agent of selection driving variation in TSD with a threshold at 210 days. Because gene flow among populations is high, such distinct patterns of geographic variation in TSD/GSD are likely maintained by contemporary selection thereby demonstrating the adaptive fine tuning of sex determining mechanisms.